Implementasi Experiential Learning Model Pada Pembelajaran Materi Shalat di SD Negeri 2 Pujodadi - Hasan, Bin; Trisnawati, Oky Ristya (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This study aims to find out how to apply the experiential model learning in prayer learning at SD Negeri 2 Pujodadi Academic Year 2023/2024 and what are the supporting and inhibiting factors in implementation experiential learning model in learning prayer at SD Negeri 2 Pujodadi For the Academic year 2023/2024, this research uses the descriptive qualitative approaches of field study that carried out in fifth grade of SD Negeri 2 Pujodadi, To obtain the data from the reseacrh, the authors conducted interviews, documentation, and observation. Data were analyzed using data reduction, displaying data, and drawing conclusions. The result of this research indicates that the experiential learning model is a model that very suitable for prayer learning at SD Negeri 2 Pujodadi because this model uses the student’s experiences that can be easier to understood by the students and students can be activated in learning. This is proven by their enthusiasm for prayer congregation for midday prayers. Besides that, experiential learning model not only prioritizing students' experiences but also creating experiences new things that make an impression on students and increase their self-confidence to students.